(untitled) (Agro Productividad, 2026)
Objective: To evaluate the effect of three Heterorhabditis nematode isolates obtained from different agroecosystems on adults of Sphenophorus incurrens, a phytosanitary problem in sugarcane (Saccharum spp.) cultivation. Design/Methodology/Approach: Adult weevils were collected from the field using bait traps and transported to the laboratory. To assess LC₅₀, LT₅₀, and the efficacy of these native nematodes, bioassays were conducted using doses of 0, 10, 50, 100, 200, 500, 1000, and 5000 infective juveniles (IJs)/adult weevil in 12-well cell culture plates over a period of 10 days. Results: All three isolates exhibited pathogenicity against sugarcane weevils at all tested doses, except the control. The most virulent strain was Heterorhabditis bacteriophora (C-23), isolated from cattle-grazed soils, with an LC₅₀ of 2,626 IJs/weevil (P < 0.0001) and an LT₅₀ of 17.7 days (P < 0.0001). Limitations/Implications: This is the first known study evaluating EPNs against adult S. incurrens under laboratory conditions. Future studies should include field evaluations of these nematodes and their target pest. Findings/Conclusions: The observed variation in weevil mortality likely relates to the ecological niche, host interaction, and life history of each nematode isolate. These findings support the potential of entomopathogenic nematodes as a viable biological control option for managing S. incurrens in sugarcane cultivation.